Rational and Emotional-Psychological Aspects of the Use of Visual Illusions in Design - Berdynskykh, Sviatoslav; Yaremchuk, Olena; Pashkevych, Kalyna (HUDPROM: The Ukrainian Art and Design Journal, 2024)
This article explores the primary directions for utilizing the potential of visual illusions and paradoxes in design and architectural practices. The study employs various research methods, including the analysis of information sources on the application of visual illusions in design, the examination of contemporary designers' works, graphic experimental modeling and composition testing, structural and systemic analysis, and synthesis of research findings. Visual illusions hold significant, yet largely untapped, potential in artistic form creation. They can attract attention to an object, shape consumer perception of the product’s desired qualities, and convey additional meanings. The aesthetic appeal of ambiguous images, dual images, and impossible figures makes them highly effective in graphic and environmental design. Illusions involving changes in perceived shape, displacement, size, mass, and deformation effects serve as an additional source of visual information. This study presents possible examples of the deliberate use of visual illusions and paradoxes to create unexpected or clever variations in visual communication, transform expected visible qualities of a product, and enhance artistic and figurative expressiveness. The research demonstrates the rational effectiveness of employing visual phenomena and highlights their potential integration with form-making techniques, taking into account the psychophysiological aspects of visual perception. By significantly expanding and systematizing the methods, directions, and techniques for applying visual illusions and paradoxes in design, this study valuable insights for design practice. The findings can be applied in the education of future professionals in artistic and creative fields, equipping them with foundational knowledge of illusions and paradoxes in design. Additionally, the research contributes to further studies in art, architecture, and design theory.